Recovery of lithium salt from spent lithium‐ion battery by less polar solvent wash and water extraction - Hao Du; Yuqiong Kang; Chenglei Li; Yun Zhao; Yao Tian; Jian Lu; Zhaoyang Chen; Ning Gao; Zhike Li; John Wozny; Tao Li; Li Wang; et al. (Carbon Neutralization, 2023)
Abstract The lithium hexafluorophosphate (LiPF6) in spent lithium‐ion batteries (LIBs) is a potentially valuable resource and a significant environmental pollutant. Unfortunately, most of the LiPF6 in a spent LIB is difficult to extract because the electrolyte is strongly adsorbed by the cathode, anode, and separator. Storing extracted electrolyte is also challenging because it contains LiPF6, which promotes the decomposition of the solvent. Here we show that electrolytes in spent LIBs can be collected by a less polar solvent dimethyl carbonate (DMC) wash, and LiPF6 can be concentrated by simple aqueous extraction by lowering ethylene carbonate (EC) content in the recycled electrolyte. Due to the similar dielectric constant of EC and water, reducing the content of EC in LIB electrolytes, or even eliminating it, facilitates the separation of water and electrolyte, thus enabling the lithium salts in the electrolyte to be separated from the organic solvent. The lithium salt extracting efficiency achieved in this way can be as high as 99.8%, and fluorine and phosphorus of LiPF6 can be fixed in the form of stable metal fluoride and phosphate by hydrothermal method. The same strategy can be used in industrial waste electrolyte recycling by diluting the waste with DMC and extracting the resulting solution with water. This work thus reveals a new route for waste electrolyte treatment and will also support the development of advanced EC‐free electrolytes for high‐performance, safe, and easily recyclable LIBs.